Peripheral hearing loss reduces the ability of children to direct selective attention during multi-talker listening - Holmes, Emma; Kitterick, Pádraig T.; Summerfield, A. Quentin (Elsevier, 2017)
Restoring normal hearing requires knowledge of how peripheral and central auditory processes are affected by hearing loss. Previous research has focussed primarily on peripheral changes following sensorineural hearing loss, whereas consequences for central auditory processing have received less attention. We examined the ability of hearing-impaired children to direct auditory attention to a voice of interest (based on the talker’s spatial location or gender) in the presence of a common form of background noise: the voices of competing talkers (i.e. during multi-talker, or “Cocktail Party” listening). We measured brain activity using electro-encephalography (EEG) when children prepared to direct attention to the spatial location or gender of an upcoming target talker who spoke in a mixture of three talkers. Compared to normally-hearing children, hearing-impaired children showed significantly less evidence of preparatory brain activity when required to direct spatial attention. This finding is consistent with the idea that hearing-impaired children have a reduced ability to prepare spatial attention for an upcoming talker. Moreover, preparatory brain activity was not restored when hearing-impaired children listened with their acoustic hearing aids. An implication of these findings is that steps to improve auditory attention alongside acoustic hearing aids may be required to improve the ability of hearing-impaired children to understand speech in the presence of competing talkers.